2020
DOI: 10.4149/km_2019_1_27
|View full text |Cite
|
Sign up to set email alerts
|

Micro-nano structure and characterization in the nugget zone of Al-Cu-Mg alloy under friction stir processing

Abstract: In this paper, the microstructure in the nugget zone of a friction-stir-processed Al-Cu-Mg alloy was analysed. There are the irregular bulk precipitates and micro-voids in the Al-Cu-Mg alloys. These precipitates were the compounds of Al-Cu system, and the size is less than 1 µm. In a local area, the homogeneous amorphous structure of Al-Cu system in some area of the nugget zone was also detected. The amorphous structure with a halo pattern has a structure characteristic of the long-range disorder. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The literature includes research by various researchers on the evolution of the microstructure and mechanical behavior of aluminum-based alloys after FSP [15][16][17][18][19][20][21][22]. These investigations have demonstrated that FSP parameters such as tool geometry, tool rotation speed, and travel speed influence the microstructure and corresponding mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The literature includes research by various researchers on the evolution of the microstructure and mechanical behavior of aluminum-based alloys after FSP [15][16][17][18][19][20][21][22]. These investigations have demonstrated that FSP parameters such as tool geometry, tool rotation speed, and travel speed influence the microstructure and corresponding mechanical properties.…”
Section: Introductionmentioning
confidence: 99%